Military Ethics : What everyone needs to know - Lucas, George R. (New York : Oxford University Press, 2016)
Why military ethics? -- The moral foundations of the military profession -- Ethics and the profession of arms -- Military ethics and international law -- The ancient origins of military ethics -- Military ethics and the just war tradition -- Military ethics apart from combat -- Ethical challenges facing the military profession -- The ethics of defense and private security contracting -- Military interventions for humanitarian relief -- Military ethics and unmanned systems -- Military ethics and cyber security -- Reconsidering ethics with the profession of arms.
Includes bibliographical references and index.
Keywords: Military ethics